Preschool children with special needs : children at-risk, children with disabilities - Lerner, Janet W.; Lowenthal, Barbara; Egan, Rosemary (Boston : Allyn and Bacon, 1998)
This book is divided into four parts: Overview; Assessment, Learning Environments, and Curricula; Intervention; and Special Issues.
Keywords: Handicapped children; Handicapped children -- Services for; Handicapped children -- Education (Preschool); Handicapped children -- Development; Preschool children -- Services for